Modelando a demanda de crédito para veículos no Brasil: Uma abordagem com mudança de regime - Mário Jorge Mendonça; Adolfo Sachsida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This study aims to analyse the demand for credit in Brazilian market for vehicles. Based on the Markov Switching model to dealing with regime change, we estimate a demand function using aggregated monthly data from Oct./2000 to Dec./2012. The results showed that the demand for credit was subject to three distinct states during this period. The first one marks the state where the credit was determined by the market fundamentals. This regime most appeared from 2004 to 2008 in which one perceives a cycle of continued and strong expansion of credit. After it follows one state strongly influenced by the economic crisis occurred in the beginning of 2008. In this period there was a great fall in credit. The third regime that rushes in a single cycle between Dec./2008 Oct./2010 happened as a result of countercyclical measures adopted by the Central Bank and the Federal Government with the aim of mitigating the effects of the economic crisis. Such measures promoted the quickly expansion of credit leading to the process of bubble formation in market for vehicles that led to the need for the introduction of so-called macro prudential measures by the Central Bank when there was already an ongoing trend of continuous increase in default.
Keywords: E32; R38; 330; credit for vehicles; demand function; Markov Switching model; bubble; default